Eskimo woman, Saint Michael, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: An Eskimo Belle, St. Michael, Alaska. 2433 Saint Michael is a village located on the east coast of St. Michael Island in Norton Sound, 43 miles southwest of Unalakleet, Yukon-Kuskokwim Delta. (pg. 827) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number